(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Coral reefs are vital ecosystems that support marine biodiversity but face increasing threats from human activities and climate change. Artificial reefs (ARs) are proposed as a mitigation strategy to replicate the functions of natural reefs (NRs). This study compares the effectiveness of ARs and NRs in supporting the abundance of Chaetodontidae indicator fish in Sental Village, Nusa Penida. A quantitative approach was applied using the Underwater Photo Transect (UPT) method to analyze coral cover and the Underwater Visual Census (UVC) to measure Chaetodontidae abundance. Data were collected from ARs, NRs, and Rubble Fields (RFs), representing degraded reef areas. The results showed that ARs had the highest coral cover (36%), followed by NRs (32%) and RFs (5%). Moderate species diversity was observed in ARs (H’ = 1,210) and NRs (H’ = 0,970), while RFs exhibited low diversity (H’ = 0.702) and high dominance (C = 0.726). ARs supported the highest Chaetodontidae abundance (0.34–0.57 ind/m²), indicating healthier coral conditions compared to NRs and RFs. Regression analysis revealed a strong positive relationship between coral cover and Chaetodontidae abundance, with a determination coefficient of R² = 0.9932. The study concluded that ARs effectively support biodiversity and Chaetodontidae abundance, although they do not fully replicate the ecological complexity of NRs. Chaetodon kleinii was identified as the dominant species across all reef types due to its high ecological flexibility. These findings underscore the importance of ARs in coral reef restoration and conservation efforts to maintain marine biodiversity.